HUBUNGAN KOMORBIDITAS DENGAN KUALITAS HIDUP & EFIKASI DIRI PADA PASIEN GAGAL GINJAL KRONIS - Lulu Bastareina; Santi Herlina (Jurnal Ilmiah Keperawatan IMELDA, 2026)
The majority of patients with chronic renal failure prefer hemodialysis as a replacement therapy for their kidney function. However, hemodialysis therapy can affect aspects of life such as physical and psychological, where one of the factors that can complicate their condition is the presence of comorbidities, namely hypertension and diabetes mellitus. In the end, these comorbidities will affect the quality of life and self-efficacy of chronic renal failure patients. The purpose of this study was to analyze the relationship between comorbidities with quality of life and self-efficacy in patients with chronic renal failure undergoing hemodialysis. The research method used was cross sectional and involved 108 chronic renal failure patients at the Pandaoni Medika Hemodialysis Clinic Jakarta. The sample determination was determined through non-probability sampling technique in the form of purposive sampling. The instruments used in this study were KDQOL-36 to measure quality of life and CKD-SE to measure self-efficacy of chronic renal failure patients. The results showed that there was a significant relationship between comorbidities with quality of life (p-value = 0.003) and self-efficacy (p-value = <0.001). The results of this study are expected to help emphasize the importance of comorbidity management to maintain good quality of life and self-efficacy.